A Rapid Total Synthesis of Ciprofloxacin Hydrochloride in Continuous Flow. (20th June 2017) - Lin, Hongkun; Dai, Chunhui; Jamison, Timothy F.; Jensen, Klavs F.
Abstract: Within a total residence time of 9 min, the sodium salt of ciprofloxacin was prepared from simple building blocks via a linear sequence of six chemical reactions in five flow reactors. Sequential offline acidifications and filtrations afforded ciprofloxacin and ciprofloxacin hydrochloride. The overall yield of the eight‐step sequence was 60 %. No separation of intermediates was required throughout the synthesis when a single acylation reaction was applied to remove the main byproduct, dimethylamine.